2004
DOI: 10.1186/1471-2156-5-19
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide diversity of the ZmPox3 maize peroxidase gene: Relationships between a MITE insertion in exon 2 and variation in forage maize digestibility

Abstract: Background: Polymorphisms were investigated within the ZmPox3 maize peroxidase gene, possibly involved in lignin biosynthesis because of its colocalization with a cluster of QTL related to lignin content and cell wall digestibility. The purpose of this study was to identify, on the basis of 37 maize lines chosen for their varying degrees of cell wall digestibility and representative of temperate regions germplasm, ZmPox3 haplotypes or individual polymorphisms possibly associated with digestibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The huge variations in association mapping population suggests that natural germplasm with a broad genetic base could be a potential resource for improving forage quality. The sample size and phenotypic variation in the current study are larger than in the previous studies of associations between lignin pathway genes and forage quality traits [ 57 60 ]. According to the population stratification, the association panel was divided into four sub-groups [ 53 ].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The huge variations in association mapping population suggests that natural germplasm with a broad genetic base could be a potential resource for improving forage quality. The sample size and phenotypic variation in the current study are larger than in the previous studies of associations between lignin pathway genes and forage quality traits [ 57 60 ]. According to the population stratification, the association panel was divided into four sub-groups [ 53 ].…”
Section: Discussionmentioning
confidence: 93%
“…In previous candidate gene-based association studies, ten lignin biosynthetic genes were investigated to detect associations between polymorphisms and forage quality traits [ 57 60 ]. The results showed that polymorphisms within the PAL , ZmC3H1 and F5H were associated with forage quality traits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two SNPs in the F5H gene, leading to a substitution from Proline to Arginine, were associated with dry matter yield (DMY) ). Finally, a miniature invertedrepeat transposable elements (MITE) insertion in the second exon of ZmPox3 was associated with cell wall digestibility in 56 inbreds (Guillet-Claude et al 2004b).…”
Section: Genes Controlling Forage Quality Of Maizementioning
confidence: 99%
“…Lignin structure and cross-linking between cell wall components influence digestibility (Barrière et al, 2003). Analysis of allelic diversity in relation to cell wall digestibility revealed ZmPox3 peroxidase, a candidate gene for silage maize digestibility improvement (Guillet-Claude et al, 2004), as it is colocalized with a cell wall digestibility and lignification QTL (Barrière et al, 2003). GBSS, starch branching enzymes 1 (SBE1) and 3 (SBE3), are major enzymes involved in starch biosynthesis in rice endosperm.…”
Section: B Genomic Resources 1 Genetic Markersmentioning
confidence: 99%